In vitro study of effects of antibiotics on Pseudomonas aeruginosa biofilm formation - Jeevajothi Nathan, Priadarssini (2017)
Pseudomonas aeruginosa has gained increasing significance as opportunistic pathogens in hospitalised patients and reported to rapidly develop resistance to numerous antibiotic classes. Furthermore, the biofilm forming ability contributes to the high resistance of P. aeruginosa to antibiotics, making the treatment of biofilm infections more difficult. This study investigated the in vitro antiplanktonic and antibiofilm activities of potential classes of antimicrobial agents includes beta-lactam-beta-lactamase inhibitor combinations, cephalosporins, carbapenems, aminoglycosides, quinolone against established P. aeruginosa biofilms. Henceforth, a total of seventy-six P. aeruginosa isolates were obtained from inpatients of Kuala Lumpur General Hospital. The antibiotic susceptibilit y profiles were determined by the minimum inhibitory concentration (MIC) using the broth microdilution method. Furthermore, biofilm forming ability was evaluated through crystal violet (CV) assay and Congo red agar (CRA). Besides, minimum biofilm inhibitory concentration (MBIC) were also assessed. A strong biofilm producing P. aeruginosa (PA-23) possessing biofilm-associated genes (pelA, pslA, algD and cupA) were chosen. This PA-23 isolate was used to observe the morphological effect of antibiotics on the biofilms using scanning electron microscopy (SEM) and determining the expression profiles of the aforementioned genes when treated with antibiotics. Among the 76 P. aeruginosa isolates, 27 isolates (35.5%) were reported as strong biofilm producer and harboured all the biofilm-associated genes. In addition, the biofilm cells showed higher resistance than planktonic cells to different antibiotics and the ratio to MBIC to MIC were found to be highest for ceftazidime and gentamicin (32-64) folds. SEM results of antibiotics treated PA-23 showed morphological changes appeared swelled, ruptured and shape alteration compared to the control which appeared normal bacilli shaped with smooth cell surfaces. The expression levels of the genes upon exposure to antibiotics showed varying expression of pelA, pslA, algD and cupA genes. In conclusion, all the above data confirm and extend the notion that ciprofloxacin, piperacillin/tazobactam and ticarcillin/clavulanic acid were potent antibiotics with clear activity against P. aeruginosa biofilms.